1988
DOI: 10.1111/j.1439-0523.1988.tb00300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritive Value of Ten Inbred Lines of Faba Beans (Vicia faba L.) in Relation to their Content of Antinutritional Constituents and Protein Quality

Abstract: Ten mbred lines of tabe beans (Vicia {aha L.) selected according to their quality characters have been investigated for carbohydrates, proteins and antinutritional compounds. Digestible energy, Nbaiance trials with growing rats comprising determination of the protein digestibility and biological value were used as criteria in connection -n-ith comprehensive chemical-biochemical analysis.The chemical composition of the ten lines show-ed a considerable diversity as did the results from the rat trials. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…These authors also found that the low-tannin varieties had higher average weights of 1000 seeds, even over 700 grams. The share of seed hull was inversely proportional to the weight of the seeds (from 12.8% in Caspar to 14.3% in Tinos) and was within the 13-15% limits given by other authors as characteristic of faba beans (Bjerg et al, 1988;Wang and Uberschar, 1990). According to Helsper et al (1993) the proportion of faba bean hulls may range from 11.6 to 15.7%.…”
Section: Weight and Basic Chemical Composition Of Seedssupporting
confidence: 81%
See 1 more Smart Citation
“…These authors also found that the low-tannin varieties had higher average weights of 1000 seeds, even over 700 grams. The share of seed hull was inversely proportional to the weight of the seeds (from 12.8% in Caspar to 14.3% in Tinos) and was within the 13-15% limits given by other authors as characteristic of faba beans (Bjerg et al, 1988;Wang and Uberschar, 1990). According to Helsper et al (1993) the proportion of faba bean hulls may range from 11.6 to 15.7%.…”
Section: Weight and Basic Chemical Composition Of Seedssupporting
confidence: 81%
“…The crude protein content of the seeds was between 27.2 and 28.9% DM, which is slightly lower than that found in most European varieties (Bjerg et al, 1988). Caspar seeds had slightly less crude protein (27.2% DM).…”
Section: Weight and Basic Chemical Composition Of Seedsmentioning
confidence: 57%
“…"Given as percent of dry matter. bReadily hydrolyzable carbohydrates, insoluble and soluble dietary fiber determined as described elsewhere (Bjerg et al 1988). The aromatic choline esters (Table 19-2) were present in group A.…”
Section: Chemical Composition Of the Products From The Processingmentioning
confidence: 99%
“…The column was Licrosorb-NH z (150 x 4.6 mm), 20 JlI of the water effluent was injected for analysis, and the mobile phase was water modified with 62% acetonitrile for oligosaccharides and water modified with 80% acetonitrile for monosaccharides. Methods of analysis for determination of chemical composition have been described elsewhere (Bjerg et al 1988).…”
Section: Chapter 13mentioning
confidence: 99%
See 1 more Smart Citation